A Dél-Dunántúli régió turizmusa 1990-2015 között: leszakadás és differenciálódás = Tourism of the region Southern Transdanubia between 1990-2015: breakaway and differentiation - Aubert, Antal; Horváth, Andrea; Jónás-Berki, Mónika; Szeidl, Klaudia (Közép-Európai Közlemények, 2017)
At the beginning of the 1990s, following the change of the political and social Systems, a new spatial structure started to develop in Hungary. Since the régimé change significant transformations have occurred in Hungárián tourism which is alsó visible at the level of the regions. Fundamental changes have occurred both territorially and structurally, induced by extemal and internál driving forces, and these changes have had different impacts on the respective regions and alsó led to differentiation within the regions. Our presentation is concentrated on the processes taking piacé in the South Transdanubian region, with the aim of exploring and analysing those factors that led to the change in the position of the region and influenced this position over the last 25 years. In addition, intra-regional processes are alsó analysed: shifts of focus and the changes taking piacé at the level of destinations.